Obligation or Desire: Variation in Motivation for Compliance With COVID-19 Public Health Guidance - Ai, Ting; Adams, Glenn; Zhao, Xian (Frontiers in Psychology, 2021)
Why do people comply with COVID-19 public health guidance? The current work considers cultural-psychological foundations of variation in beliefs about motivations for such compliance. Specifically, we focused on beliefs about two sources of prosocial motivation: desire to protect others and obligation to the society. Across two studies, we observed that the relative emphasis on desire to protect others (versus obligation to the community) as an explanation for compliance was greater in U.S. settings associated with cultural ecologies of abstracted independence than in Chinese settings associated with cultural ecologies of embedded interdependence. We observed these patterns for participants’ explanations of both others’ (Study 1) and own (Study 2) psychological experience, and for compliance with mandates for both social distancing and face masks (Study 2). Discussion of results considers both practical implications for motivating compliance with public health guidance and theoretical implications for denaturalizing prevailing accounts of prosocial motivation.